A masked ritual: wedding night virginity test among Sri Lankan muslims - Naleefa, Abdul Wadood Noor; Mimi Hanida Abdul Mutalib,; Yew Wong, Chin (Penerbit Universiti Kebangsaan Malaysia, 2023)
The virginity test in the wedding bed is a widespread custom in many cultures and Sri Lanka is no exception. Wedding night virginity testing among Muslim community is camouflaged and masked but prevails. As a result, this study was created to investigate the significance, explanations, relevance, and reasoning for the Muslim marital virginity test as a marriage custom. This study is wholly qualitative. In order to gather data, nine cases were studied in-depth using the snowball sampling technique. One focus group discussion and five key informant interviews were done. The study has shown that the entire virginity test for the bridal bed is a pointless, damaging, humiliating, and unfair practice. The concept of hymenoplasty is barely understood by respondents. Several terms are used to describe virginity tests, such as potti odakkiya (cracking box), pon kulippaattal (bride bathing), etc. The celebration of the virginity test is marked with a breakfast feast, gifts such as gold jewelry, etc. The wedding bed virginity test has been viewed as a harmful habit, encouraging feelings of inferiority and decreasing self-worthiness. Despite gender inequalities, it was proposed that the community at large be educated about the unreliability of wedding bed virginity tests. This study fills a research gap and contributes much-needed empirical data to the academic world by providing an explanatory review on the wedding bed virginity test among Sri Lankan Muslims.